2017
DOI: 10.1016/j.hbrcj.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of replacing sand by iron slag on physical, mechanical and radiological properties of cement mortar

Abstract: In the present study, the effects of replacing sand by high percentages of basic-oxygen furnace slag on the compressive strength, bulk density and gamma ray radiation shielding properties of mortar have been investigated. Cement mortar of mix proportion 1:3 including various percentages of iron slag was designed. The percentages of replacement were 0%, 40%, 80% and 100% by weight of fine aggregate. Mortar mixes were prepared with water cement ratio of 0.44 and cured in potable water for 90 days. The attenuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The elongation of TS aggregates allowed a greater depth of embedment while their angularity improved the bond within the matrix. Similar results were reported by Ouda and Abdel-Gawwad [35] and Guo et al [36]. Ouda and Abdel-Gawwad observed that the rough surface and angularity of oxygen furnace slag aggregate are attributed to the progressive contribution of strength up to 100% replacement.…”
Section: Compressive Strengthsupporting
confidence: 88%
“…The elongation of TS aggregates allowed a greater depth of embedment while their angularity improved the bond within the matrix. Similar results were reported by Ouda and Abdel-Gawwad [35] and Guo et al [36]. Ouda and Abdel-Gawwad observed that the rough surface and angularity of oxygen furnace slag aggregate are attributed to the progressive contribution of strength up to 100% replacement.…”
Section: Compressive Strengthsupporting
confidence: 88%
“…Half-value layer is usually used to assess the effectiveness of a material as radiation shielding. An HVL is the material thickness value needed to reduce the intensity of an X-ray beam to half of the initial intensity [16].…”
Section: The Effect Of Pb-nitrate Filler Addition On the Attenuation Coefficient And Hvl Of Composite Apronmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that steel slag has good physical characteristics, such as high strength and durability, which shows a potential to be used as aggregates in the construction industry [12,13]. Consequently, the use of industrial byproducts by the construction industry can contribute to solve problems of lack of aggregates in several locations and reduce environmental problems related to mining [14]. So, the civil construction sector is one of the industries that are most interested in the use of this type of waste and seeks to incorporate it in construction materials, aiming to improve the properties of its products, reduce production costs, and generate less environmental impact.…”
Section: Introductionmentioning
confidence: 99%